Ion energy and angular distributions in RF capacitively coupled plasma sources - Manuilenko, O.V.; Minaeva, K.M. (Вопросы атомной науки и техники, 2006)
The possibilities to control ion energy distribution functions (IEDFs) and ion angle distribution functions (IADFs) on electrodes in single- and dualfrequency capacitively coupled plasma (CCP) sources are investigated by means of particle-in-cell/Monte Carlo (PIC/MCC) simulations. It is shown that the IEDFs can be controlled by the driven voltage and frequency in singlefrequency capacitive discharges. It is demonstrated that the IEDFs and IADFs can be controlled by the low frequency voltage in dualfrequency CCP sources.